STRUKTUR DAN FUNGSI SOSIAL CERITA RAKYAT LEGENDA INYIAK SUSU SABALAH DI KANAGARIAN KOTO GADANG KECAMATAN TANJUNG RAYA KABUPATEN AGAM - Devi, Mayona Sri; Hasanuddin WS, Hasanuddin WS (Jurnal Bahasa dan Sastra, 2019)
This research is aimed to describe: (1) the structure of folklore legends Inyiak Susu Sabalah in Koto Gadang Village, West Tanjung Raya, District Agam; and (2) the social function of folklore legends Inyiak Susu Sabalah in Koto Gadang Village, West Tanjung Raya, District Agam. This sort of research is a qualitative study using descriptive methods. This research data is structure and social function of folklore legends Inyiak Susu Sabalah in Koto Gadang Village, West Tanjung Raya, District Agam. Data is collected from informants through two stages, that is (1) recording folklore legends Inyiak Susu Sabalah, and (2) data collection about storytelling environment. The data were analyzed by the steps of: (1) a data inventory phase; (2) classification of data; (3) the stage of discussion or conclusion from data classification results; and (4) the stage of reporting. Based on the research, was found the following statements. (1) The structure of folklore legends Inyiak Susu Sabalah in Koto Gadang Village, West Tanjung Raya, District Agam including: (a) language style; (b) characterization; (c) background; (d) storyline; (e) theme; and (f) mandate. (2) Social functions contained in folklore is inheritance of oral traditions, owner’s society identity, and social control.Keywords: legends, Inyiak Susu Sabalah, Minangkabau